The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3390/ijms18122556
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Chlorin e6-Cobalt Bis(Dicarbollide) Conjugate in Balb/c Mice with Engrafted Carcinoma

Abstract: The necessary precondition for efficient boron neutron capture therapy (BNCT) is control over the content of isotope 10B in the tumor and normal tissues. In the case of boron-containing porphyrins, the fluorescent part of molecule can be used for quantitative assessment of the boron content. Study Objective: We performed a study of the biodistribution of the chlorin e6-Cobalt bis(dicarbollide) conjugate in carcinoma-bearing Balb/c mice using ex vivo fluorescence imaging, and developed a mathematical model desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These substances dispose of many important properties such as chemical and thermal stability [ 17 ], rigid geometry, delocalized negative charge, ion-pairing behavior [ 18 ], strong acidity of their conjugated acids [ 19 ], solubility in water and oils [ 20 ], ability to self-assembly into monolayer spherical nano-vesicles [ 21 , 22 ], non-specific interaction with the protein surface and high affinity to albumin [ 23 , 24 ]. The most studied area of application for heteroboranes in biological sciences is boron neutron capture therapy used for the treatment of locally invasive malignant tumors [ 23 , 25 , 26 ]. In addition, these substances have proven capability to inhibit some liver microsomal enzymes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These substances dispose of many important properties such as chemical and thermal stability [ 17 ], rigid geometry, delocalized negative charge, ion-pairing behavior [ 18 ], strong acidity of their conjugated acids [ 19 ], solubility in water and oils [ 20 ], ability to self-assembly into monolayer spherical nano-vesicles [ 21 , 22 ], non-specific interaction with the protein surface and high affinity to albumin [ 23 , 24 ]. The most studied area of application for heteroboranes in biological sciences is boron neutron capture therapy used for the treatment of locally invasive malignant tumors [ 23 , 25 , 26 ]. In addition, these substances have proven capability to inhibit some liver microsomal enzymes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a mathematical model was developed that accurately describes the accumulation and distribution of CCDC in tissues. The model's high fit with the experimental data suggests its reliability and usefulness in understanding and predicting the behavior of boron accumulation and distribution in various organs [217].…”
Section: Chlorin-containing Compounds For Anticancer Therapymentioning
confidence: 87%
“…These compounds exhibited high phototoxicity in human lung A549 cells upon light irradiation [ 51 ]. Studies in tumor-bearing mice showed that compound 15 accumulated preferentially in the tumor with a T/N ratio of about 3:1, 3 h after IV injection of the sensitizers [ 52 ].…”
Section: Porphyrin Derivatives For Bnctmentioning
confidence: 99%